2012
DOI: 10.1016/j.compbiomed.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Deep and surface hemodynamic signal from functional time resolved transcranial near infrared spectroscopy compared to skin flowmotion

Abstract: The potential disturbance in the prefrontal cortex hemodynamic signal measured by functional near infrared spectroscopy (NIRS), due to forehead skin flowmotion, detected by laser Doppler flowmetry, was investigated by a standard protocol of hemodynamic challenge by Valsalva maneuver, aimed at assessing and disentangling local regulatory responses in skin vasomotion and in cerebral perfusion in presence of a strong systemic drive, and to quantify the common information in the two signals. The deep cortical NIRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Finally, the level of [THb] recorded in this study (baseline VMO [THb] = 148.5 ± 6.8 μM) is consistent between subjects, indicating similar distribution of muscle in the sample volume. While the influence of superficial changes in blood flow and blood volume on reported kinetics cannot be discounted(8), others have shown these to be minimal in the case of brain TR-NIRS measurements (1). Furthermore, it has been shown that using spatially-resolved NIRS, another technique capable of compensating for changes in PL, reduces sensitivity to skin blood flow in muscle [THb] measurements(25).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the level of [THb] recorded in this study (baseline VMO [THb] = 148.5 ± 6.8 μM) is consistent between subjects, indicating similar distribution of muscle in the sample volume. While the influence of superficial changes in blood flow and blood volume on reported kinetics cannot be discounted(8), others have shown these to be minimal in the case of brain TR-NIRS measurements (1). Furthermore, it has been shown that using spatially-resolved NIRS, another technique capable of compensating for changes in PL, reduces sensitivity to skin blood flow in muscle [THb] measurements(25).…”
Section: Discussionmentioning
confidence: 99%
“…Solutions to circumvent this problem are constantly being sought, and currently include inter-channel subtraction using additional NIRS measurements from short source-detector separations (sensitive mainly to superficial layers) to remove the extracerebral interference present in longer source-detector separations (Gagnon et al, 2012), new analytical methods and post-processing algorithms, development of advanced spectroscopic methods (SRS, time-resolved systems; Aletti et al, 2012) and hybrid technologies (Gunadi and Leung, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have raised the issue of superficial - extra-cortical - contributions in NIRS signals, specifically in the O 2 Hb signal [62]. The analysis of the photon time-of-flight distribution in time-domain NIRS [63], [64] or the use of additional short emitter-detector separation as regressors [65], [66] have been proposed as methods to separate cortical and extracortical contributions in NIRS signals. In the study described here, the clear variability in attention decrement-sensitivity across the cortical areas investigated does not support the idea of a global systemic response biasing the feature space.…”
Section: Discussionmentioning
confidence: 99%